The Potential to Build Collective Capacity for Organisational Learning in the Context of Teachers' Use of Digital Technology for School Improvement - Susila Davis-Singaravelu (MDPI AG, 2022)
This article considers how digital spaces focused on whole school improvement combined with supportive leadership may be mobilised towards building collective capacity for evidence-informed practice and organisational learning. This topic originated from a qualitative, multi-method design-based research (DBR) project that studied practitioners' use of an online resource for primary school practitioners called Pathways for school improvement, designed by Oxford University Press (OUP). Semi-structured interviews, participant observations and a documentary analysis were conducted with teachers and senior leaders in five primary schools across England between 2014 and 2016. Connections were made with the dynamic approach to school improvement (DASI) that encourages practitioners to systematically engage with a variety of evidence in their reflections and efforts to design school and classroom improvement strategies. Pathways' four-step system and series of systematised tasks under each step seemed to provide opportunities for practitioners to explore elements of theory and practice in conjunction with empirical and pupil performance data, and potentially guide them through how to collaborate with others in developing specific whole school approaches to improvement. Opportunities and challenges in developing collective capacity for improvement are also explored.